Risk assessment of Ebola Reston virus in humans in the Philippines - Johnette A Peñas; Mary Elizabeth Miranda; Vikki Carr de los Reyes; Ma. Nemia L Sucaldito; Rio L Magpantay (World Health Organization Regional Office for the Western Pacific, 2019)
Objective: There have been five documented outbreaks of Ebola Reston virus (RESTV) in animals epidemiologically linked to the Philippines. This assessment was conducted to determine the risk of RESTV occurring in humans in the Philippines and its potential pathogenicity in humans. Methods: The World Health Organization Rapid Risk Assessment of Acute Public Health Events Manual was used for the assessment. A literature review was done and a risk assessment matrix was used for the risk characterization of the outbreaks in the Philippines. The risk assessment was conducted by the Philippines Field Epidemiology Training Program. Results: The risk of RESTV occurring in humans in the Philippines and its potential pathogenicity in humans were both assessed as moderate. Animals involved in RESTV outbreaks in the Philippines were non-human primates and domestic pigs. The presence of RESTV in pigs poses a possibility of genetic evolution of the virus. Although RESTV has been identified in humans, there was no death or illness attributed to the infection. The Philippines Inter-agency Committee on Zoonoses oversees collaboration between the animal and human health sectors for the prevention and control of zoonoses. However, there is no surveillance of risk animals or previously affected farms to monitor and facilitate early identification of cases. Discussion: The moderate risk of RESTV recurring among humans in the Philippines and its potential pathogenicity in humans reinforces the need for early detection, surveillance and continued studies of RESTV pathogenesis and its health consequences. The One Health approach, with the involvement and coordination of public health, veterinary services and the community, is essential in the detection, control and management of zoonosis.